Does the use of antenatal corticosteroids reduce respiratory morbidity in babies born in late preterm period? - Khadijah A. Shittu; Bolaji Ahmed; Kabiru Afolarin Rabiu; Fatimat Akinlusi; Oluwarotimi I. Akinola (BMC, 2024)
Abstract Background The aim of this study is to determine the effectiveness of antenatal corticosteroid in reducing respiratory morbidity in babies born in the late preterm period. Methods Two hundred and eighty-six pregnant women at risk of having a late preterm delivery were studied. One hundred and forty-three (143) served as the cases and were given 2 doses of 12 mg intramuscular dexamethasone 12 h apart, while 143 served as the controls and were given a similar quantity of placebo. The women were followed up prospectively and data were collected on the pregnant women and their newborns on a standardized form. The neonates were assessed for acute respiratory distress syndrome and transient tachypnea of the newborn based on clinical signs, symptoms, and chest x-ray results (when indicated). The primary outcome was the occurrence of neonatal respiratory morbidity. Results The primary outcome occurred in 5 out of 130 infants (3.8%) in the dexamethasone group and 31 out of 122 (25.4%) in the placebo group (P value = 0.000003). Birth asphyxia, neonatal intensive care admission and need for active resuscitation at birth also occurred significantly less frequently in the dexamethasone group (P value 0.004, 0.009, 0.014 respectively). There were no significant group differences in the incidence of neonatal sepsis, neonatal jaundice, hypoglycemia and feeding difficulties. Conclusions Administration of dexamethasone to women at risk for late preterm delivery significantly reduced the rate of neonatal respiratory complications, neonatal intensive care unit admission, and need for active resuscitation at birth. Trial registration PACTR ( www.pactr.org ) Registration Number: PACTR202304579281358. The study was retrospectively registered on April 19, 2023.